English: the elite language for the elites - Dina Aprianti (IRecall Journal, 2024)
The notion of Elite multilingualism is deeply related to the current status of the English language in Indonesia as a foreign language, but it is highly desired due to the prestige and power attached to the language. Those who are proficient in English are likely to be hired rather than individuals who do not have the proficiency and it gives access for students to enrol to reputable universities. However, the prestige embedded with English has declined the users of Bahasa Indonesia and social inequality is inevitable due to the limited access to English learning. This essay aims to illuminate what makes English an elite language belongs to the elites by reflecting on relevant literature.